Investigating Accounting Students' Comprehension During Online Learning: a Case Study in a Muslim University - Tenriwaru; Nor Shafiqah; Kirana Ikhtiari (Yayasan Rumah Peneleh, 2023)
This research aims to explore students' understanding of introduction to accounting courses during online learning. The type of research used by the researcher is descriptive research with a qualitative approach. There were obstacles found that consist of unsipported network, and lack of students' understanding of material provided especially in practice making financial reports. Although, there were some advantages from online learning such as more efficient learning costs, for example for boarding, transportation as well as food, and that online learning provides more practical solution, the results of research indicate that such learning mode in a Muslim university was less effective.